The Influence of Population Size, Economic Growth, and Regional Minimum Wage on the Unemployment Rate in the Regencies and Cities of Bakorwil 1 Madiun - Handri Dona; Sri Hartono; Wijianto (Nomico, 2024)
A resident is someone who has lived in a country for a long time. The problem that often occurs in a country is about unemployment. Unemployment is a problem that has not yet been resolved. The role of the government is urgently needed in reducing the unemployment rate. Population numbers that are not resolved properly can cause economic development goals to not be achieved. Economic success is seen from improving economic growth and decreasing inequality in a region. This study aims to examine the effect of Population Number, Economic Growth and Regional Minimum Wage on Unemployment Levels in the Regency/City of the Bakorwil 1 Madiun Region. This study uses quantitative methods. , where the required data is obtained from BPS. The results showed that the Independent Variable Population (X1) had no partial and significant effect on the unemployment rate, economic growth (X2) had a partial and significant effect on the unemployment rate, and the regional minimum wage (X3) had no partial and significant effect on the unemployment rate. the unemployment rate in the Regency/City of the Bakorwil 1 Madiun Region.